A clinical case with Anti-MOG associated demyelinating disease - D. A. Bazhenova; E. I. Zaydullina; A. A. Malkova; N. V. Komissarova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Anti-MOG-associated diseases are a relatively new and poorly studied group of autoimmune demyelinating disorders. Description of clinical cases helps to expand the understanding of the pathology, its diagnosis and treatment. The relevance of the article also lies in the demonstration of diagnostic algorithms, including the use of specific markers (anti-MOG antibodies) and neuroimaging methods (MRI). Despite the growing interest in this pathology, the number of described cases remains limited. Objective: to study a clinical case with antiMOG-associated demyelinating disease and to identify the relevance of this disease in our time. Materials and methods: a clinical case provided in the neurological department of the Republican Clinical Hospital No. 1, Izhevsk. Results. Upon discharge, the following diagnosis was made: "Demyelinating disease of the central nervous system with the phenotype of ZONM (myelitis with complete regression of symptoms against the background of GC therapy), anti-AQP 4(-) (anti-MOG-associated disease) in the form of mild coordination disorders, mild subcortical syndrome, optic neuritis on the right, asthenic-subdepressive syndrome." Conclusions. Anti-MOG-associated demyelinating disease is relevant at present, positive dynamics are observed during treatment.